(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The Cameron-Walker graphs are the graphs for which their matching number equals their induced matching number. In this paper, we study lower bounds for the graph energy in terms of induced matching numbers for the general graphs with equal matching and induced matching number. Moreover, we study the lower bounds of the graph energy of Cameron-Walker graphs.